1987
DOI: 10.1007/bf00594195
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of posttransfusion recoveries achieved with either fresh or stored platelet concentrates

Abstract: The effectiveness of platelet concentrate transfusion depends on such variables as blood bag material, donor--recipient compatibility, and time elapsed between donation and transfusion. To study the latter a corrected thrombocyte increment for recovery in the recipients was evaluated with 108 platelet transfusions in 31 patients. In 83 treatment programs, the mean recovery at the one-hour post-transfusion time point was 8.6 X 10(9) platelets/l with fresh platelets and 5.9 X 10(9) platelets/l with stored platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The age of the platelet component is often regarded as affecting clinical efficacy 29,30 . However, the studies that support this concept 29,30 report that only those platelets transfused less than 24 to 48 hours after collection appear to be more efficacious than older platelets, and usually only in certain situations, such as refractoriness due to infection. However, in most United States centers, it is not possible to transfuse platelets less than 48 hours after collection, because of testing, labeling, and distribution constraints.…”
Section: Discussionmentioning
confidence: 99%
“…The age of the platelet component is often regarded as affecting clinical efficacy 29,30 . However, the studies that support this concept 29,30 report that only those platelets transfused less than 24 to 48 hours after collection appear to be more efficacious than older platelets, and usually only in certain situations, such as refractoriness due to infection. However, in most United States centers, it is not possible to transfuse platelets less than 48 hours after collection, because of testing, labeling, and distribution constraints.…”
Section: Discussionmentioning
confidence: 99%
“…O'Connell et al [9] infused their platelet dose within 30 min, but practically, most intravenous therapists infuse platelets for an hour or more, though it has been advised to transfuse platelets within 10-20 min [28]. Most studies give no indication as to the length of time for their platelet infusions, nor to the length of platelet storage, which also impacts platelet counting methods [29].…”
Section: Discussionmentioning
confidence: 99%
“…Longer platelet storage times have been reported to decrease posttransfusion platelet viability. [20][21][22][23] However, some investigators have suggested that storage adversely affects only platelet concentrates rather than apheresis platelets. 24 In our study, an equal benefit of platelets stored for 48 hours or less was seen for all the types of platelets transfused.…”
Section: Org Frommentioning
confidence: 99%